Social Inequality And Disaster: A Sociological Analysis of The Impact of Social Class-Based Disasters - Evi Diana Sari; Baiq Lily Handayani (Department of Sociology Faculty of Social and Political Sciences, 2022)
This paper focuses on the social inequalities of catastrophic societies that occur due to social class differences. Upper class people have a lot of access to disaster relief from the government so that social jealousy arises in the lower class who feel injustice because of uneven assistance from the government that even encountered cases of disaster relief corruption. The impact of disasters is so great that in this case the government must be serious in addressing this problem of social inequality so that there is no conflict in disaster communities. This condition if not immediately overcome by the government can prevent the community to recover from the disaster. This phenomenon is analyzed through social class theory and conflict theory to describe the conditions of inequality of catastrophic societies. Based on analysis conducted by previous researchers found that there are social class differences that have the potential for conflict in disaster communities. This research method uses review literature obtained from previous books, articles or journals. The purpose of this writing is to explain how social inequality can occur in disaster societies.